Trade policies of India : a quantitative analysis - Panchamukhi, V. R. (Delhi : Concept, 1978)
The main focus of the study has been on the quantitative aspect of the analysis of trade policies Several quantitative approaches were used largely to derive a better insight into the problem and to demonstrate the need for quantitative analysis of the entire policy system in India.
Includes index.
Bibliography: p. [296]-312.
rpm 21/01/2019
Loans
Keywords: Trade; Trade policies; India